Settlement analysis of foundation soil over a long time and comparison with field performance - Karim, M.R.; Gnanendran, C.T. (2009)
This paper models the consolidation of the foundation soil of a wide geogrid reinforced embankment close to its centre-line. An elastic viscoplastic model has been used for the analysis. A creep function that takes into account of the non-linear nature of creep has also been incorporated in this model. The predicted results are compared with the field measurement data and with the analysis results obtained using two other models (i.e. Kutter and Sathialingham, 1992 and modified Cam-Clay).